Collecting Duct Sodium Reabsorption in Deoxycorticosterone-Treated Rats - John A. Haas; Theresa J. Berndt; Stephen P. Youngberg; Franklyn G. Knox (The Journal of Clinical Investigation, 1979)
In vitro studies of isolated, perfused, cortical collecting tubules have demonstrated that prior chronic deoxycorticosterone acetate (DOCA) treatment increases sodium reabsorption in this nephron segment, yet sodium balance in vivo is maintained. To evaluate the effect of chronic DOCA treatment on collecting duct sodium reabsorption in vivo, we compared fractional sodium delivery (FDNa%) out of the superficial late distal tubule with the fraction of sodium remaining at the base and the tip of the papillary collecting duct during extracellular fluid volume expansion in untreated, salt-treated, and DOCA-salt-treated rats. In untreated rats, FDNa% to the distal tubule was 6.5±1.0%, and to the base was 8.7±1.6% (Δ2.2±0.9%, P < 0.05). FDNa% to the tip was 4.9±1.1%, significantly less than FDNa% to the base (Δ3.7±1.1%, P < 0.01). In salt-treated rats, FDNa% to the distal tubule was 8.3±0.8%, and to the base was 10.4±1.1%. FDNa% to the tip was 5.9±0.6%, significantly less than FDNa% to the base (Δ 4.6±1.0%, P < 0.005). In DOCA-salt-treated rats, FDNa% to the distal tubule was 16.1±2.6% and to the base was 9.5±1.9% (Δ 6.6±1.7%, P < 0.005). FDNa% to the tip was 5.9±1.2%, also significantly less than FDNa% to the base (Δ 3.6±1.1%, P < 0.01). We conclude that (a) in DOCA-salt-treated rats, sodium delivery to the end of the superficial distal tubule is greater than in untreated or salt-treated rats; (b) in DOCA-salt-treated rats, sodium delivery to the end of the superficial distal tubule is greater than to the base of the papillary collecting duct, suggesting stimulation of sodium reabsorption in the cortical and(or) outer medullary collecting duct; and (c) sodium reabsorption by the papillary collecting duct is unaffected by chronic DOCA-salt treatment in the volume-expanded rat.